2014
DOI: 10.1161/circimaging.113.001541
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Location, Size, and Transmurality of Chronic Myocardial Infarction Without Exogenous Contrast Media by Using Cardiac Magnetic Resonance Imaging at 3 T

Abstract: Background LGE CMR is a powerful method for characterizing MI, but the requisite gadolinium infusion is estimated to be contraindicated in nearly 20% of MI patients due to end-stage chronic kidney disease. The purpose of this study is to investigate whether T1 Cardiovascular-Magnetic-Resonance Imaging (CMR) obtained without contrast agents at 3T could be an alternative to Late-Gadolinium-Enhanced (LGE) CMR for characterizing chronic myocardial infarctions (MIs) using a canine model of MI. Methods and Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 54 publications
6
54
0
Order By: Relevance
“…Recent studies in a canine model of MI have shown that native T 1 mapping at 3-T can reliably characterize chronic MIs and can therefore be a potential alternative to LGE CMR (12). In this study, we investigated the clinical validity of the canine findings in 2 pilot patient populations with prior STEMI and NSTEMI, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent studies in a canine model of MI have shown that native T 1 mapping at 3-T can reliably characterize chronic MIs and can therefore be a potential alternative to LGE CMR (12). In this study, we investigated the clinical validity of the canine findings in 2 pilot patient populations with prior STEMI and NSTEMI, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, a CMR approach that could visually detect and quantify chronic MI without exogenous contrast media would be immensely valuable in the overall diagnosis and management of MI patients. Using a canine model of reperfused chronic MI, we previously demonstrated that native T 1 mapping at 3-T provides significantly greater sensitivity and specificity for characterizing chronic MI over native T 1 mapping at 1.5-T (12). In this study, we examined whether native T 1 Patients were excluded from the study if they had symptoms of chest pain, electrocardiogram changes, or cardiac enzyme elevation within 1 year before the date of CMR examination; multiple infarctions; or were contraindicated in a magnetic resonance study (claustrophobia, metallic implants, glomerular filtration rate <45 ml/min/1.73 m 2 , and so on).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Visual assessment of the native T1 parametric maps was undertaken to look for areas of focal increased signal that likely indicate replacement fibrosis (23,24).…”
Section: Visual Assessment Of Native T1 Mapsmentioning
confidence: 99%
“…Fishers exact test confirmed there was a significant difference between HD and controls groups for areas of discrete mid-wall or insertion point hyperintensity (P=0.026). Figure 3 shows the mid-ventricular end-diastolic cine MRI and native T1 maps of 1 control and 3 HD patients with progressively increasing native T1 times (23).…”
Section: Visual Assessment Of Native T1 Mapsmentioning
confidence: 99%